Evaluation of Stress Generated with Different Abutment Materials and Angulations under Axial and Oblique Loading in the Anterior Maxilla: Three-Dimensional Finite Element Analysis. (1st December 2021) - Kapoor, Sumedha; Rodrigues, Shobha; Mahesh, M.; Shetty, Thilak; Pai, Umesh; Saldanha, Sharon; Hedge, Puneeth; Shenoy, Satish
Abstract : Purpose . The aim of this study was to assess and correlate the stress distribution in an anterior maxillary implant-supported prosthesis with 0°(degree), 15°, and 25° angulated titanium and zirconia abutments using a three-dimensional (3D) finite element analysis (FEA). Materials and Methods . Six FEA models consisting of a dentate anterior maxilla with a single bone-level implant of dimension 4.2 × 10 mm placed in the region of left maxillary central incisor and abutments of dimension 4.2 mm made of titanium and zirconia each with angulation 0° (IA and IB), 15° (IIA and IIB), and 25° (IIIA and IIIB) and ANSYS Workbench software were utilized to design a layered zirconia crown. Unilateral axial and oblique loads of 178 N were applied on the palatal aspect of the crown of left maxillary central incisor. Average von Mises stress values were evaluated in the implant and the peri-implant bone quantitatively and qualitatively. Results . Stress was shown to increase with an increase in angulation in all the areas that were examined. Zirconia abutments showed lesser stress in the implant and surrounding bone than titanium abutments. When compared with the body and apex of the implant, the implant neck values were higher in all models. In between cortical and cancellous bone, the stress recorded was higher in the cortical bone. Conclusion . Within the limitations of this study, straight abutments generated a more uniform and minimal stress in implant and peri-implant bone than angulated abutments. Titanium abutments generated higher stress levels than zirconia abutments. The stresses generated are directly proportional to an increase in abutment angulation, and therefore, straight abutments are most suitable for favourable stress transmission.